Religious renunciation of a pastoral people - Srivastava, Vinay K. (Delhi ; New York : Oxford University Press, 1997)
Religion of the Rabaris of the Rajasthan, India; a study.
Includes bibliographical references (p. [281]-306) and index.
Keywords: Rabaris -- India -- Rajasthan; Renunciation (Philosophy)